Preparation and characterization of beads of fish scales hydroxyapatite/collagen /silver nanoparticles by using infiltration method - Mudhafar, Mustafa (Tanjung Malim, 2021)
Preparation and characterization of beads of fish scales hydroxyapatite/collagen /silver nanoparticles by using infiltration method by Mudhafar, Mustafa